Reuse of electronic equipment and software installed on them: An exploratory analysis in the context of circular economy - Cristian Bogdan Onete; Irina Mărunţelu; Răzvan Dina (Amfiteatru Economic Journal, 2018)
The transition to a circular economy in which the value of products, materials and resources is maintained as long as possible and the waste is minimized, has led to the creation of new business opportunities and new, innovative and efficient production and consumption models. Over the last few years, the principles of the circular economy have been gradually integrated into several sectors, the consumer electronics industry being such an example. The applicability of the circular economy principles in this sector has been presented in the literature, but these approaches have taken into account, in particular, the physical, tangible components of electronic products, focusing on the existing interrelationships between the circular economy and the production and use of electronic devices and equipment. Given that electronic products often incorporate intangible components, namely the software necessary for their operation, we have chosen to address in this paper the problems of the circular economy from this perspective, the purpose of this paper being to emphasize the relation between the use of software products and the principles of circular economy. Thus, the paper presents the main opportunities and challenges that circular economy involves for all stakeholders, namely manufacturers of electronic goods and developers of the related software and their users. In order to determine the way consumers capitalize the possibilities to reuse the software components of IT products they use (computers, tablets, mobile phones), we have undertaken an exploratory research that took place between October and November 2017 on the basis of a structured questionnaire posted online and applied to Romanian young people, the number of respondents being 257. Research has shown the respondents easily adapt to new versions of software when they change their phone or laptop and there is a frequent transfer of equipment without considering the possibilities of reuse the software because when the respondents alienate these devices also delete the installed software.
Keywords: L17; L63; L86; 330; circular economy; electronic equipment; software; software license; free and open source software (FOSS)